Exploring Brown and Levinson's Politeness Strategies: An Explanation on the Nature of the Politeness Phenomenon - Putri Adrian Sapitri; Aprilia Chasanah; Avivah Adinda Putri; Jessica Paulima (REiLA : Journal of Research and Innovation in Language, 2020)
This study aimed at reviwing brown levinson politeness strategies purposed in their book (1978) entitled "POLITENESS (Some Universals in Language Usage)". Over the past three decades, there has been a significant increase in research on politeness strategies from social and linguistic aspects. This is evident from the many papers that appear on this issue in international journals and monographs. Brown and Levinson (1978) developed a theory to explainphenomena related to the Politeness on verbal communication and non-verbal. This article For methods using a content analysis approach as a qualitative in research. Which has been studied in the book Brown & Levinson This article is interested in focusing on the types of politeness strategies put forward by Brown and Levinson (1978). This present study sees politeness stretegies proposed by brown and levinson still can be used in current situation related politeness both verbal and non verbal communication.